From the Ancient Eudaimonia to Modern Indices: A Critical View - Diakomihalis, Mihail (Issues in Economics and Business, 2022)
GDP (Gross Domestic Product) is an index that has been used by all free economy countries for almost a century. However, it has been criticized by many researchers and politicians for its misleading messages about the real wealth of people, its inability to evaluate the effect of environmentally harmful activities, the well-being of societies, the exclusion of non-market activities which exist in all economies, and the non-transactional services provided by the natural environment. This study aims to analyze and evaluate GDP and ten more alternative indicators as to their Simplicity, Comprehensibility, Completeness and Reliability, using a questionnaire addressed to experts, i.e., university professors. SWB (Subjective Well-Being) has been assessed as the preferred index for an overall evaluation, while the FSI (Failed States Index) ranks in the last position. GDP received its highest ranking as second in Reliability, with Gross National Income (GNI) ranking first. SWB refers to and evokes the direct democracy of 5th century Athens with its Simplicity, Comprehensibility, and Completeness, but not for its Reliability, due to the difficulty of its measurement. A combination of SWB with GNI might produce a reliable GDP alternative.